Disease responses of hexaploid spring wheat (Triticum aestivum) culms exhibiting premature senescence (dead heads) associated with Fusarium pseudograminearum crown rot - Knight, Noel L.; Macdonald, Bethany; Percy, Cassy; Sutherland, Mark W. (European journal of plant pathology, 2021)
Hexaploid spring wheat ( Triticum aestivum ) may exhibit significant crown rot disease responses to infection by Fusarium pseudograminearum , with a range of susceptibility levels available in commercial cultivars. Dry conditions during grain-fill may lead to the expression of prematurely senescing culms, which typically fail to set grain. Assessment of hexaploid spring wheat plants exhibiting both non-senescent and prematurely senescent culms was performed using visual discolouration, F. pseudograminearum biomass and vascular colonisation in culm sections sampled at three different heights above the crown and at the peduncle. Samples from six commercial cultivars were collected at milk development in 2014 from Narrabri and Tamworth, New South Wales and Wellcamp, Queensland. Prematurely senescent culms exhibited greater visual discolouration, F. pseudograminearum biomass and vascular colonisation than non-senescent culms in each cultivar. A further comparison of the parameters across four time points from milk development, when senescent culms are first observed, to maturity was conducted for cultivar Sunlin. F. pseudograminearum biomass and vascular colonisation were significantly different between culm conditions prior to maturation, while visual discolouration was not significantly different between culm conditions at any single time point. Colonisation of xylem and phloem tissue was extensive in the basal portions of prematurely senescent culms (36 to 99%) prior to maturation, and suggests significant impacts on water and nutrient movement during crown rot disease. Despite a range of resistance ratings being assessed, cultivars were not reliably separated based upon responses to severe disease pressure, demonstrating the continuing need for improved crown rot resistance in commercial wheat.